The triple realm of AI-enabled education: from instrumental rationality to value reconstruction‌ - Zihao Wan; Bingyao Xie; Yuxi Hou (Journal of Exploration of Vocational Education, 2025)
Artificial Intelligence (AI) is reshaping the education ecosystem, and its development presents the triple realm of "instrumental rationality - integration rationality - value rationality". The instrumental rationality stage optimises teaching efficiency through technology, but faces the risk of alienation of teachers' roles and data privacy; the integration rationality stage emphasises human-computer collaboration to promote personalised learning and educational equity, but needs to solve the problems of technological ethics and system integration; the value rationality stage focuses on the reconstruction of the essence of education, and advocates that AI empowers moral and humanistic education, and balances technological efficiency and humanistic care. The current challenges include algorithmic bias, digital divide and lack of ethical governance, which need to be addressed through interdisciplinary integration, policy synergy and teacher capacity enhancement. In the future, AI education will evolve towards generative intelligence, lifelong learning and sustainable development, and it is necessary to build an inclusive ecosystem to ensure that technology empowers educational equity and social value.